Pemberdayaan Peternak Lebah Apis cerana melalui Pelatihan Pengolahan dan Pengemasan Madu Hutan Berbasis Higiene Sanitasi di Dusun Petung Bondowoso - Faiqatul Hikmah; Niswatin Hasanah; Erfan Kustiawan; Yoswenita Susindra; Zilvahisna Emka Fitri (Utami Publisher, 2026)
Petung Hamlet, located in Kretek Village, Bondowoso Regency, possesses considerable potential in the development of forest honey derived from local Apis cerana bees. However, traditional harvesting, processing, and packaging practices have resulted in suboptimal product quality and limited market competitiveness. This community service program aimed to improve the knowledge and technical skills of local beekeepers through training on hygienic honey processing and packaging based on food sanitation principles and Good Manufacturing Practices (GMP). The program was implemented using a participatory approach consisting of problem identification, field observation, preparation of standard operating procedures (SOP), training, mentoring, and evaluation. The results demonstrated an increase in participants’ understanding and awareness regarding hygienic processing techniques, proper packaging methods, and product quality improvement. In addition, the introduction of a manual centrifugal honey extractor supported more efficient and hygienic honey extraction practices. The program contributed to strengthening local honey product competitiveness, increasing community empowerment, and supporting sustainable rural economic development based on local forest resources.